Reorienting Khatam Al-Qur’an: From Ritual Ceremony to Social Tafsir Revitalization in Minangkabau - Faruq Aziz Al Amin; Citra Indriani (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2025)
This study aims to examine the shifting orientation of the Khatam Al-Qur’an tradition in Minangkabau from a religious rite toward a socially performative ceremony, and to explore possibilities for its revitalization through a social tafsir perspective. Rooted in the Minangkabau maxim adat basandi syarak, syarak basandi Kitabullah, Khatam Al-Qur’an historically marked a child’s completion of Qur’anic recitation and functioned as a medium of religious internalization. In contemporary practice, however, it has increasingly become a display of social prestige—often pejoratively labeled Katam Ayam—raising concerns about the erosion of its spiritual substance. Employing qualitative library-based research and drawing on the Tafsir Adabi Ijtima‘i approach, this article situates the tradition within broader debates on the tension between spirituality and cultural performance in Muslim societies. The analysis demonstrates that Khatam Al-Qur’an embodies both continuity and rupture in the negotiation of religious meaning. The study argues that revitalization efforts must reorient the tradition toward tadabbur-centered engagement with the Qur’an, in line with the principle al-muhafazah ‘ala al-qadimi al-shalih wal-akhḏu bil-jadīd al-aṣlaḥ. Such reorientation can restore Khatam Al-Qur’an as a locus of Qur’anic literacy, moral education, and cultural resilience, harmonizing local wisdom with the Qur’an’s universal ethical vision.